Heart rate variability during pre-competition and competition periods in volleyball players - Podstawski, R.; Boraczynski, M.; Nowosielska-Swadzba, D.; Zwolinska, D. (Biomedical Human Kinetics, 2014)
Regular exercise training is thought to modify cardiac autonomic control. One of the body`s responses to training stimuli is heart rate variability (HRV). The use of HRV in the management of sport training is a common practice. The objective of the present study was to assess the impact of the physical activity level on HRV of 1st league national volleyball players prior to and during the competition period. Materials and methods: The study involved 11 players whose HRV was evaluated during the two analysed training periods. Selected indicators of spectral analysis (total power, %VLF, % LF, % HF powers, LF n.u, HF n.u, and LF/HF powers) as well as time analysis (HR, RR, RMSSD, NN50) were assessed on the basis of recordings. Results: The studies conducted in the pre-competition and competition periods showed significant differences in the parameters of spectral VLF% analysis and time NN50 analysis. In the competition period, a significant increase in VLF [%] may be the result of increased psycho-physical arousal, when compared to the pre-competition period. Conclusions: Resting bradycardia, assessed on the basis of time analysis indicators, may be the result of internal changes in the sinus node, which reflects the impact of long-term training on the cardiac conduction system. A high level of physical activity of volleyball players in the tested periods could have contributed to a reduction in vagal tone and a shift in the balance of the autonomic nervous system in the direction of the sympathetic system, which may be the result of overtraining.